Difficulties In Learning Noun Clauses by Students in Intermediate English Grammar Classroom - Imtihan Hanim; Diah Retno Anggraini (JOLADU: Journal of Language Education, 2023)
Grammar appears to be unavoidably challenging for most L2 learners, particularly when it comes to acquiring noun clause. A noun clause is a dependent phrase that functions similarly to a noun. It has been a difficult area for EFL university students at Muhammadiyah University of Tangerang. The purpose of this study was to discover the students' challenges in learning noun clauses and how they dealt with their issues. The chosen participants were 25 students from the Intermediate Grammar Class in 2022. The method of the research was qualitative. The data was collected through doing interview. The data revealed that students had three major difficulties interpreting noun clauses. Recognizing functions, creating noun clauses, and identifying the subject and verb of a noun phrase were all tough. In addition, three strategies were employed by students to overcome learning barriers. They were going through materials, asking peers, looking for information, and exercising on the Internet.